Organization of sympathetic innervation of interscapular brown adipose tissue in the mouse. Issue 9 (16th December 2021) - Huesing, Clara; Zhang, Rui; Gummadi, Sanjeev; Lee, Nathan; Qualls‐Creekmore, Emily; Yu, Sangho; Morrison, Christopher D; Burk, David; Berthoud, Hans Rudolf; Neuhuber, Winfried; Münzberg, Heike
Abstract: The interscapular brown adipose tissue (iBAT) is under sympathetic control, and recent studies emphasized the importance of efferent sympathetic and afferent sensory or humoral feedback systems to regulate adipose tissue function and overall metabolic health. However, functional studies of the sympathetic nervous system in the mouse are limited, because details of anatomy and fine structure are lacking. Here, we used reporter mice for tyrosine hydroxylase expressing neurons (TH:tomato mice), iDISCO tissue clearance, confocal, lightsheet, and electron microscopy to clarify that (a) iBAT receives sympathetic input via dorsal rami (instead of often cited intercostal nerves); (b) dorsal rami T1–T5 correspond to the postganglionic input from sympathetic chain ganglia (stellate/T1–T5); (c) dorsal rami serve as conduits for sympathetic axons that branch off in finer nerve bundles to enter iBAT; (d) axonal varicosities show strong differential innervation of brown (dense innervation) versus white (sparse innervation) adipocytes, that surround the core iBAT in the mouse and are intermingled in human adipose tissues, (e) axonal varicosities can form neuro‐adipocyte junctions with brown adipocytes. Taken together, we demonstrate that sympathetic iBAT innervation is organized by specific nerves and terminal structures that can be surgically and genetically accessed for neuromodulatory purposes. Abstract : The interscapular brown adipose tissue (iBAT) innervations reaches their targets via dorsal rami, not via intercostal nerves (aka ventral rami). Dorsal rami 1–5 represent sympathetic chain ganglia inputs (stellate ganglion to T5). Fine nerves branch off each dorsal ramus to enter the iBAT for innervation, while dorsal rami continue to innervate additional dorsal structures like the skin. Brown adipocytes (BA) are densely innervated by axonal varicosities that form neuro‐adipocyte junctions, while white adipocytes show sparse innervation in mouse and human adipose tissues. Core iBAT innervation density remains unchanged by cold exposure, but increases in white adipose tissue mainly within beige islands.